Gene-Gene Interactions among Pparα/δ/γ Polymorphisms for Apolipoprotein (Apo) A-I/Apob Ratio in Chinese Han Population. - Bo Hai (Iranian Journal of Public Health, 2014)
The peroxisome proliferator-activated receptors (PPARs) -α, -δ/β and -γ are the ligand-activated transcription factors involved in the regulation of fatty acid and lipoprotein metabolism, energy balance, cell proliferation and differentiation and atherosclerosis, etc. We investigated the associations of 10 single-nucleotide polymorphisms (SNPs) in PPARs with apolipoprotein (apo) A-I/apoB ratio in Chinese Han population.Overall, 630 subjects (212 males, 418 females) were randomly selected from the Prevention of Metabolic Syndrome and Multiple Metabolic Disorders in Jiangsu Province of China Study Cohort. Population analyzed was as the general population which involved healthy people and individuals with disorders of apoA-I or apoB. 10 SNPs (rs1800206, rs135539, rs4253778, rs2016520, rs9794, rs10865710, rs1805192, rs709158, rs3856806 and rs4684847) were genotyped. Mean difference (Difference) and 95% confident interval (95%CI) were calculated.After covariates adjustment, rs1800206-V allele (LV+VV) and rs3856806-T allele (CT+TT) were significantly associated with a decreased apoA-I/apoB ratio than those wild type carriers, Difference (95%CI) were -1.29 (-1.96-0.62) and -0.8 (-1.42~-0.17), respectively. Rs4253778-C allele was significantly associated with an increased apoA-I/apoB ratio compared to the wild type carriers (GG), Difference (95%CI) was 0.76 (0.04-1.48). Generalized multifactor dimensionality reduction analysis showed that three-to-eight-locus models were significant with apoA-I/apoB ratio (P